Application of High Tech Architecture Principles Richard Rogers in the Design of a Science and Technology Center in Pekanbaru - Muhamad Iqbal; Muhd Arief Al Husaini; Mashuri (PT FORMOSA CENDEKIA GLOBAL, 2023)
Along with the development of the era, the growth of science and technology is happening so fast. In supporting the development of science and technology, the Indonesian government issued a policy to develop a Regional Science and Technology Center (PP-IPTEK) as a fun science and technology learning facility. The Science and Technology Center in the city of Pekanbaru is expected to be a means of supporting educational activities and introducing Science and Technology to the public in an interesting way. This design uses a High-Tech Architecture approach that supports the function of this building as a recreation area based on education and technology. This architectural approach gives the building a modern and visionary form for the future. There are several types of analysis used in this design, that is analysis of humans, environment, buildings, and analysis of high technology-based buildings.